Simulasi Jenis Penyakit Pasien yang Berobat Menggunakan Metode Monte Carlo - Lubis, Romia (Jurnal Sistim Informasi dan Teknologi, 2022)
The Community Health Center (Puskesmas) is a functional health organization in providing comprehensive and integrated services to the community. This organization is a community health development center that fosters community participation in improving public health services funded by the government. As the first health facility in providing health services, the Puskesmas is often visited by many patients who arrive at the same time. The number of patient visits that are too many is inversely proportional to the health workers who are on duty. This causes the ongoing health services to be less than optimal. To improve these services, identification of the type of disease is carried out so that better services can be prepared. The purpose of this study is to predict the type of disease in the future. The data on the types of diseases that were processed in this study from 2019 to 2021 were sourced from the Silaping Health Center. The data is processed by the Monte Carlo method. The results of this study are predictions of types of diseases in the future tend to increase every month, so that the Puskesmas must prepare more medical personnel who have expertise in their fields. This information can be used as a reference in the application of manpower to higher institutions to improve services. Thus, this system is very helpful in improving services by making it easier to identify needs for the future